2003
DOI: 10.1046/j.1432-1033.2003.03775.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein farnesyltransferase inhibitors interfere with farnesyl diphosphate binding by rubber transferase

Abstract: Rubber transferase, a cis-prenyltransferase, catalyzes the addition of thousands of isopentenyl diphosphate (IPP) molecules to an allylic diphosphate initiator, such as farnesyl diphosphate (FPP, 1), in the presence of a divalent metal cofactor. In an effort to characterize the catalytic site of rubber transferase, the effects of two types of protein farnesyltransferase inhibitors, several chaetomellic acid A analogs (2, 4-7) and a-hydroxyfarnesylphosphonic acid (3), on the ability of rubber transferase to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Based on this possibility and the results presented herein, high-affinity inhibitors may be preferred to substrates as probe molecules. Rubber transferases are effectively inhibited by protein farnesyltransferase inhibitors in vitro with species-specific differences (Mau et al, 2003). Interspecies differences, observed here as well, suggest that selection of probes for photo-labeling experiments might be tailored to the species for best results.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Based on this possibility and the results presented herein, high-affinity inhibitors may be preferred to substrates as probe molecules. Rubber transferases are effectively inhibited by protein farnesyltransferase inhibitors in vitro with species-specific differences (Mau et al, 2003). Interspecies differences, observed here as well, suggest that selection of probes for photo-labeling experiments might be tailored to the species for best results.…”
Section: Discussionmentioning
confidence: 61%
“…As noted in earlier work with natural isoprenoid diphosphates (Cornish and Siler, 1995;Cornish et al, 1998) our results with Bz-modified initiators demonstrate that biosynthetic rate increases with increasing length of allylic pyrophosphate molecule. This has been shown to be true even for protein farnesyltransferase inhibitors (Mau et al, 2003) where lengthening the hydrophobic moiety of analogues increased the binding affinity of the inhibitor for the substrate binding site. We demonstrate that additional structural or stereochemical factors also play a role in recognition by rubber transferases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcripts encoding other proteins related to rubber biosynthesis (Table 3) were identified in guayule using the Hevea sequences for comparison, including farnesyl pyrophosphate synthase (FPPS), which synthesizes FPP, an initiator of rubber biosynthesis both in vivo and in vitro (Tanaka et al, 1996;Castillon and Cornish, 1999;Mau et al, 2003). Another Hevea protein homolog identified in our EST-deduced protein sequences, although not at as high abundance as in Hevea, is SRPP.…”
Section: Isoprenoid Pathway and Rubber Biosynthesis Related Transcripmentioning
confidence: 99%
“…13 Vederas, instead, in an effort to characterize the FPP binding site of rubber transferase showed that 1 is able to inhibit, in vitro , rubber biosynthesis promoted by rubber transferase from Hevea Brasiliensis . 14 Besides, the same author found that 1 was also able to reduce the activity of the PBP1b (penicillin-binding protein 1b), albeit with modest potency. 15 Recently, Sabbatini has shown that the inhibition of the Ras/ERK1/2 pathway by 1 resulted in a beneficial effect on acute ischemia-reperfusion injury in rats, preserving either renal function and histology.…”
Section: Introductionmentioning
confidence: 98%